Confronting China. - Kaplan, Robert D. (National Interest)
The article focuses on confronting relations of China with the U.S. and humanitarianism is for the American brand and Muslims do not yearn for democracy as much as they yearn for dignity and justice. It mentions American foreign policy elite does not like to talk about culture since culture cannot be quantified and hope of understanding foreign affairs. It also mentions computer hacking, espionage, port building and expansion, the movement of navy and fishing fleets, and on all appear coordinated. It reflects on China could weaken internally due to economic upheavals causing its leaders to dial up nationalism as a default option.